UNRECOGNIZED MYOCARDITIS FOR LIFE AS THE CAUSE OF SUDDEN CARDIAC DEATH OF A FOOD DELIVERY SERVICE WORKER: MYOCARDITIS AS THE CAUSE OF SUDDEN CARDIAC DEATH OF A FOOD DELIVERY SERVICE WORKE - stefanović, ivana; Sindjelic, Vladimir; Andjelic, Sladjana; Tasic-Uros, Danijela; Milivojcevic-Bevc, Ivana; Colakovic, Goran (Halo 194 Scientific Journal of Emergency Medicine, 2023)
Case report The emergency medical assistance team was sent for medical intervention because of a younger person lying in the corridor of the building without signs of life. Heteroanamnestically, information was obtained about delivery to the fifth floor of a building without an elevator. Cardio-pulmonary resuscitation was started, which was unsuccessful. Due to the fatal outcome in a public place, the police were called, and the body was sent for an autopsy, where myocarditis was histologically recorded. Conclusion: Myocarditis is an insufficiently recognized cause of sudden death in young people. Future research should be focused on adopting more precise criteria for lifetime detection of myocarditis in such high-risk occupations.
Keywords: Myocarditis; cardiac arrest; delivery workers